QUALITY OF LIFE IN PATIENTS WITH INVASIVE BLADDER CANCER AFTER RADICAL CYSTECTOMY AND URINARY DIVERSION - Komiljonov K. D.; Allamova Sh. M.; Shukurov M. Kh. (Modern American Journals, 2025)
Background. Radical cystectomy remains the gold standard for the treatment of muscle-invasive bladder cancer (MIBC). However, the choice of urinary diversion has a significant impact not only on surgical outcomes but also on long-term quality of life (QoL).
Keywords: Invasive bladder cancer, radical cystectomy, cutaneous ureterostomy, ileal conduit, urinary diversion, quality of life